Pengaruh Pendidikan Kebencanaan Terhadap Perilaku Kesiapsiagaan Bencana Gempa Bumi Di Mts Muhammadiyah 6 Bayat - Tasha Vima Eka (Geography Education Study Program, Universitas Kanjuruhan Malang, 2020)
Klaten Regency as one of the regencies in Central Java Province is prone to natural disasters such as earthquakes, floods, landslides, droughts and tornadoes. The purpose of this mitigation education is to teach disaster learning properly and correctly so that students are able to be prepared for disaster threats in the school environment. The population in this study were 100 school residents. The school residents are 85 students, and 15 teachers in MTs Muhammadiyah 6 Bayat, Klaten Regency. Sampling using a random sampling technique with Slovin method. The results showed that the students of Mts Muhammadiyah 6 Bayat still had quite low knowledge about disaster preparedness.